Does corporate social responsibility (CSR) impact on development of women in small-scale fisheries of sub-Saharan Africa? Evidence from coastal communities of Niger Delta in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2018)
While women are often key actors in fisheries, they are commonly excluded from making fisheries management decisions, often due to cultural norms. The objective of this investigation is to assess the impact of a new CSR model of multinational oil companies (MOCs) on development of women in small-scale fisheries in the Niger Delta region of Nigeria. A total of eight hundred artisanal fisherwomen were sampled across the coastal communities of Niger Delta. Results from the use of logit model indicate that artisanal fisherwomen have remained widely excluded from the General Memorandum of Understandings (GMoUs) interventions in small-scale fisheries due to cultural norms of the people. This implies that if the cultural norms of the Niger Delta communities continue to restrain direct participation of the artisanal fisherwomen from GMoUs ' intervention, achieving gender equity and cultural change would be limited in the region. The findings suggest that since fisheries, which is the traditional source of livelihood of the people are no longer viable and have significant ly declined due to environmental oil degradation, GMoUs ' intervention structure could focus on women playing key roles in fisheries management and conservation decision in Niger Delta region of Nigeria.
Keywords: 330; Inequality; Corporate social responsibility; Multinational oil companies; Logit model; Coastal communities; Artisanal fisherwomen; Nigeria